THE IMPLEMENTATION OF QUESTION AND ANSWER TECHNIQUE TO TEACH THE TENTH GRADE STUDENTS IN WRITING RECOUNT TEXT IN MA MA’ARIF NU DRIYOREJO GRESIK (RETAIN, 2014)
THE IMPLEMENTATION OF QUESTION AND ANSWER TECHNIQUE TO TEACH THE TENTH GRADE STUDENTS IN WRITING RECOUNT TEXT IN MA MA’ARIF NU DRIYOREJO GRESIK Firasari Fajarwati English Department, Faculty of Languages and Arts, State University of Surabaya firsa.soetikno@yahoo.com Drs. H. Aswandi M.pd English Department, Faculty of Languages and Arts, State University of Surabaya Abstract As a productive skill, writing has an important role to help the students to be able to communicate especially in indirect communication. The teacher must be creative in teaching of writing. Question and answer technique is suggested to be used as a technique in teaching writing. The teacher used recount text. In this study, the research questions consist of two questions; they are (1) how is the implementation of question and answer technique to teach the tenth grade students’ writing skill of recount text in MA Ma’arif Gresik? (2) how is the students’ responses after the implementation of question and answer technique? A teacher can use questions whether it is oral or written questions. It is to stimulate thinking and light the way to productive learning and retention of content material (Vacca, 1981: 159). Questions encourage students to think. Thinking can arise the students’ interest and questions can also be used to evaluate. As the result of this function, it is believed that questions can direct someone’s choice of ideas and activities, and can transform the often different topics from a scattered survey of the subject, problem, or theme into logical, coordinated for attaining knowledge. Based on the reason above, the researcher conducts this research about the implementation of question and answer technique to develop the tenth grade students’ writing ability to write recount text in MA Ma’arif NU Driyorejo, Gresik, especially in X-1 class. The research design of this study is descriptive qualitative. The purpose of research design is to describe the activities of the teacher and the students in teaching and learning process during the implementation of question and answer technique in writing class. To collect the data, the researcher observes the implementation of question and answer technique in teaching and learning process. Then, she got the result of students’ writing in every meeting. And the last, she collect the students’ responses from questionnaire. After that, she analyzes all data in every meeting based on phenomenon that happen in teaching and learning process. The result of data analyzed, it can be seen that the students of X-1 had done the assignments well in every meeting. In each meeting, the students improve their writing ability. Applying question and answer technique in writing class can make the students improve their writing, especially in writing recount text. It can be seen from the students’ responses the questionnaire. Almost all students said that they can improve their ability and it can motivate them to learn a foreign language, especially in writing class. It can be concluded that question and answer technique can be recommended as one of an alternative techniques in teaching writing. Because it can help the students develop their writing ability and can reduce boring situation in teaching and learning process. Keywords: Writing, Question and Answer Technique, Recount Text, Tenth Grade INTRODUCTION One way of learning foreign language is through writing. Not many centuries ago, writing was a skill in educational or religious institutions. Nowadays, written language has many functions in everyday life. They are particularly for action, information and entertainment. Sokolik (2003: 88) in Practical English Language Teaching states that writing is both physical and mental act. Nunan (2003: 88) writes out the definition of writing as a series of contrast: It is both physical and mental act. Physical act deals with committing words or ideas to some medium. Whereas mental act deals with the ability to invent ideas, express them, and how to organize them into a good writing which is clear to the reader. Its purpose is both to express and impress. Writing has a purpose to express ideas or feeling to the readers in order that the readers will be impressed with a writer’s thought. It is both a process and product. In writing, there are some processes that are involved including collecting ideas, organizing, drafting, editing, and reading. Those will be very helpful in producing a good writing product. The last definition brings us to the explanation of the writing process. Langan (2005: 64) explains that there are three main steps which can help a writer create a good composition: Pre-writing In this stage, a writer will be able to think on a paper and to gradually discover what ideas that will be developed. Langan explains further that there are five techniques that will help a writer to develop ideas; they are: (1) free writing, which is a brainstorming activity in which a writer can write out every phrase or sentence that come up into mind about possible topics, (2) questioning, which can be an effective way of getting a writer to think about a topic from a number of different angles, which includes What? Why? Where? When? Who? and How? This technique is the one which is studied by the researcher, (3) making a list, in which the writer collects the ideas and details related to the subjects and makes it as a list without trying to sort the major details from minor ones, (4) clustering, which is also known as diagramming or mapping to show the relationship among ideas and detail that occur, (5) making an outline, in which the writer thinks carefully about the point that she will make. Drafting This is the part where the writer starts writing the complete thought that has been collected composition, including the introductory, the body, and the conclusion. Revising Here, the writer begins to revise the composition that has already been made. This stage can be done by rewriting, building on what has already been done, in order to make it stronger. Furthermore, writing is an important part of people’s life for communication. Kelly (1999: 84) states that writing which forever defines communication in the written words is the important form of communication because it can be a solution when spoken communication is not possible. Byrne (1990: 1) supports that writing is one of language skill, which is used for medium of communication, especially indirect communication. People usually use indirect communication because of some problems; for instance: distance, time, activity, etc. by using indirect communication, they can still deliver their message. The Indonesian government gives attention to teach writing by making the English curriculum properly. The curriculum clearly states writing is one skill of learning English (BNSP, 2006: 164). Moreover, writing is a basic language skill of learning English which is important. The students need writing skill to convey their ideas in writing reports, scientific writing, short stories, etc. in the educational field. Unfortunately, many students are not interested in writing because, according to them, writing is difficult. The difficulty comes from the limited time for such an assignment that takes a continuous thinking process. However, it is still an important skill that a learner needs to master. Bramer (1981: 4) states that writing will continue to be an important part of a student’s life, especially in college course and in many careers and profession. It is a skill which can make someone be recognized by the society , the schools, and objective language studies. One genre of texts taught in senior high school is recount text. The social function of recount text is to retell an activity, situation, or event in the past. Language features used in recount text is past tenses, action verbs, adverb of past time. The researcher believes that teaching writing is far more difficult than mastering the writing skill itself. Healon (1991: w135) states that writing skill is complex and sometimes difficult to teach, requiring not only of grammatical and theoretical devices, but also it has conceptual and judgment elements. Based on this problem, the researcher suggested this question and answer technique which could improve the students’ ability in writing. Dealing with teaching and learning process, a technique is essential. A technique that is needed in a writing class is the one that can ease and helps the students to produce a composition. The researcher believed that the best way to stimulate ideas of the students who are learning to make a composition is by giving questions. Questions are used as an indicator of people doubt, which has occurred in his reasoning. Some people can express their thought easily, but some others cannot. It is because each person has different experience. Another influence comes from the person’s psychological state. We can always find a case in a classroom where there are some students who keep the questions for themselves for fear of decision. Questions and answers are essential components of teaching and learning. Asking a good question will help the teacher to motivate students’ curiosity about the topic, and it will help the teacher assesses how well they understand the materials. When constructing sentences, the students were given a series of questions. The complete answers of the questions are then constructed in a certain way to make a well-organized recount composition. RESEARCH METHOD This research is a descriptive qualitative research. This design is used to examine the events or the phenomena that happened in teaching and learning process, especially to get the data about the implementation of question and answer technique to develop student’s writing. The subjects of the study were the teacher and the tenth grade students of MA Ma’arif NU Driyorejo, Gresik. The teacher is Agus Setiono, S. Pd. And there were 30 students of class X-1. The researcher will use three instruments in this study; they are (1) observation checklist, which contains some indicators, such as the teaching and learning process, the topic, and the question and answer technique, (2) field notes, which is a brief note made by researcher to observe the teaching and learning process, and (3) questionnaire, which is useful for the researcher to gather the students’ responses. The data gathered from the teaching and learning process in the subject’s classroom. The data will be collected through non-participant observation. Therefore, the researcher will only observe and make documentation out of the teaching and learning activities. The data will be interpreted in a descriptive manner in which the researcher describes the information which are collected with the instruments. RESULTS AND DISCUSSION After analyzing all the data, the researcher presents the result and also the discussion which is based on the theories which the researcher was elaborated previously. The Implementation of Question and Answer Technique In the first and second meeting, the teacher started the class with opening session by greeting the students. The teacher then asked the students’ feeling that day. He also checked the attendance list and asked the students to prepare the lesson. The teacher asked the students about their knowledge of kinds of texts, especially recount text. Then he continued to ask the students’ prior knowledge and related information about recount text. In the first meeting, the students could not answer the teacher’s questions completely, so the teacher needed to explain. The teacher explained everything about recount text; the definition, the generic structure, and the language use. In the second meeting, the teacher only reminded them at a glance because they had enough explanation on the first meeting. In the teaching and learning process, only in the first meeting the teacher introduced the technique used. Because it was the first time they applied this technique. He introduced the concept of question and answer technique in writing recount text. The teacher explained the procedure of the technique deliberately and the students paid attention. He also gave the example of how to elaborate the answers on whiteboard. In both meeting, the teacher gave the students question and answer paper. He asked the students to answer the questions on the paper and then elaborated the answer to make a recount text. The teacher asked the students to finish the task on time. The teacher controls the students’ interaction in the teaching and learning process. He asked the students to do the task by themselves. He walked around and asked the students to do the task quietly. He also helped students who had difficulties. In the first and second meeting, the students had done all the steps of question and answer technique. However, in the first meeting, some students still find difficulties in writing recount text. It can be seen from the students who could not use time effectively. The teacher asked to submit their work, but some students had not finished yet. But in the second meeting, they could use time more effectively. Most of them got interested in writing recount texts based on their experiences. After the students submitted their works, the teacher corrected them. The teacher then showed their mistakes in their assignments. He also gave some corrections to the students. The teacher explained the students’ mistakes in details. It means that he gives feedback to the students. The students paid attention to the teacher’s explanation about their mistakes. They took some notes on their notebooks. From the data of the observation, it is obvious that the implementation of question and answer technique was very effective to teach writing recount text. It helps to motivate the students and bring and interest in teaching and learning process. Question and answer technique became a better way that provided a wide opportunity for the teacher and the students to interact each other in an enjoyable learning situation. The Students’ Responses The students’ responses towards the implementation of question and answer technique were positive from the result of the questionnaire. The percentage of the students who likes learning English is more than 50%.most of the students enjoy writing recount text by using question and answer technique. More than half of the students did not find any difficulties in writing recount text by using question and answer technique. They also did not find any difficulties in using vocabulary and language feature. The result of questionnaire showed that the application of question and answer technique was appropriate to overcome the students’ difficulties in writing recount text. Based on the explanation above, it is clear that the students’ ability had progressed in writing recount text. Most of the students could create a better composition than their previous composition. It showed that this technique is effective in improving the students’ skill in expressing their ideas into written form. CONCLUSION AND SUGGESTION Conclusion In general, the implementation of question and answer technique in teaching writing in every meeting was quite good. The students could enhance their language skill. This technique is the efficient way to learn about writing, especially in writing recount text. By using this technique, the students have the same opportunities to improve their writing and develop their ideas to write a recount text. It can be concluded that question and answer technique could bring interest to the students in composing a recount text. The response of the students toward the implementation of question and answer technique in teaching writing recount text was positive. The result of the questionnaire shows that most of the students are interested in this technique. They said that this technique was unique that it can reduce their boredom in the normal monotonous classroom activities. Most of the students admitted that they find themselves improving their ability in writing recount text. Suggestion After interpreting and analyzing all the data, the researcher has suggestions for several groups of readers who have similar interest. Using a variety of technique in teaching a foreign language will increase the students’ interest in learning. It will also motivate them more to be actively involved in classroom activities. Therefore, English teachers should not be afraid of implementing every teaching technique provided by the experts. Being a creative teacher will bring effectiveness in teaching and learning process. However, it does not mean to neglect the process of choosing the appropriate materials for them. It will only disturb their confidence in completing every assignment given. This research is conducted to get to know deeper about a technique that has been developed by experts. Therefore, for other researchers who have an interest in investigating more about this technique, the researcher strongly recommends to conduct a research on this technique in different language skills or in different text genres. REFERENCES Abbot Gerry, Greenwood john, Mc Keating Douglas and Wingard Peter. 1981. The Teaching of English as an International Language: A Practical Guide. Great Britain. William Collin Sons and Co Ltd. Adam, Jager. 1998. Beginning to Write. USA: Massachusets, Institute of Technology. Airey, J. 2002. The Way We Do It. English Teaching Professional. http://www.etprofessional.com, retrieved February 28, 2011. Alice, and Hogue, Ann. 1991. Writing Academic English. London: Longman. Alice, and Hogue, Ann. 1999. Introduction to Academic Writing. Weasley Publishing Company Inc. Anderson, Mark, and Kathy, A. 1998. Text Type in English 2. Australia: MacMillan Education Pty Ltd. Bram, Barli. 1995. Write Well: Improving Writing Skill. Yogyakarta: Kanisius. Bramer, George R and Sedley, Dorothy. 1981. Writing for Readers. New York: Bell and Howell Company. Byrne, Donn. 1980. Teaching Writing Skill. London: Longman Group Ltd. Carter, Bishop, and Kravits. 2002. Keys to Effective Learning. 3rd Edition. New Jersey: Pearson Education Inc. Comrie, Bernard. 1985. Tense. Cambridge: Cambridge University Press. Creswell, John W. 2008. Educational Research: Planning, Conducting, and Evaluating Qualitative and Quantitative Research. United States of America: Pearson Prentice Hall. Depdiknas. 2005. Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Atas dan Madrasah Aliyah. Jakarta: Depdiknas. Depdiknas. 2006. Standar Isi: Standar Kompetensi Lulusan Mata Pelajaran Bahasa Inggris (SD, SMP, MTS, SMA, MA, SMK). Jakarta: Depdiknas. Derewianka, Beverly. 1990. Exploring How Text Works. Australia: Primary Teaching Association. Doddy, Ahmad et al. 2008. Developing English Competencies for Senior High School (SMA/ MA). Jakarta: Pusat Perbukuan Depdiknas. Doddy, Ahmad et al. 2008. Look Ahead: An English Course for Senior High School Students Year XI, Science and Social Study Program. Jakarta: Pusat Perbukuan Depdiknas. Harmer, Jeremy. 2001. The Practice of English Language Teaching. Harlow: Pearson Education Limited. Heaton, J. B. 1997. Writing English Language Test. London: Longman. Heffernan and Lincon. 1982. Writing: A College Handbook. 1st Edition. USA: W. W. Norton & Company Inc. Hogue, Ann. 2003. The Essential of English (A Writer’s Handbook). New York: Pearson Education Inc. Kagan, Spencer. 1989. The Structural Approach to Cooperative Learning. San Juan Capistrano. Kendall, Julie. 2006. Writing Sense. Portland: Publisher. Krisner, Laurie G, and Stephen R. Mendell. 1987. Basic College Writing. 1st Edition. USA: W. W. Norton & Company. Lado, Robert. 1964. Language Teaching: A Specific Approach. New York: Mc Graw Hill Publishing Scientific Co. Ltd. Lado, Robert. 1977. Language Testing: The Construction and Use of Foreign Language Test. London: Longman Group Ltd. Langan, John. 2000. English Skills. Singapore: Mc Graw-Hill Companies Inc. Langan, John. 2005. College Writing Skills. 6th Edition. The Mc Graw-Hill Companies Inc. Larsen-Freeman, Diane. 2003. Teaching Language: From Grammar to Grammaring. Boston: Heinle. Mc Millan, J. H. 1992. Educational Research: Fundamental for the Consumers. New York: Harper Collin. Mc Worther and Mc Combs. 2001. Write to Read, Read to Write. New York. Meyers, Allan. 2001. Gateway to Academic Writing; Effective Sentences, Paragraph and Essay. NY: Longman. Morreillon, Judi. 2007. Strategy for Teaching Writing. Chicago: American Library Association. Murray, Donald. 1972. Teach Writing as a Process not Product. The Leafleft. Nunan, David. 1996. The Self Directed Teacher, Managing the Learning Process. United States of America: Cambridge University Press. Nunan, David. 1999. Second Language Teaching and Learning. Boston: Heinle and Heinle Publishers. Nunan, David. 2003. Practical English Language Teaching. Singapore: Mc Graw Hill. Petty, T. Walter and Sensen, M. Julie. 1980. Developing Children’s Language. New York: Pearson Education Inc. Raimes. 1983. A Technique in Teaching Writing. New York: Oxford University. Reid, M. Joy. 1993. Teaching ESL Writing. New Jersey: Regents Prentice Hall. Richards, Jack C et al. 2002. Methodology in Language Teaching. Cambridge: Cambridge University Press. Sugiono, 2005. Metode Penelitian Kualitatif. Bandung: CV Alfabeta Choir. Tarigan, Henry Guntur. 1986. Menulis Sebagai Suatu Keterampilan Berbahasa. Bandung: Angkasa. Trevor, Rob. 1998. Educational Leadership. Alexandria: Association for Supervision and Curriculum Development. White, Ron and Valerie Arndt. 1991. Process Writing. England: Longman House. Wilhem, Jeffrey D. 2007. Engaging Readers and Writers with Inquiry. New York: Scolastic. Wingard, P. 1981. The Teaching of English as an International Language: A Practical Guide. London: William Collin Sons and Co Ltd.